2017
DOI: 10.1103/physrevb.95.165414
|View full text |Cite
|
Sign up to set email alerts
|

High-energy exciton transitions in quasi-two-dimensional cadmium chalcogenide nanoplatelets

Abstract: Semiconductor nanoparticles of cadmium chalcogenides are known to exhibit pronounced thickness-dependent E0 series of exciton transitions at the Γ point of the Brillouin zone (BZ). In this work, we report an experimental evidence for high-energy series of exciton transitions, which originates from BZ points different from the Γ point, in the family of cadmium chalcogenide quasi-2D nanoplatelets (NPLs). Intensive UV absorption bands demonstrating a pronounced size effect are observed for CdTe, CdSe, and CdS NPL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…As shown in Ref. 22, energetically the most favorable position of these surface atoms are the bridge positions in which the halogen atoms enter the positions of the missing selenium atoms in the ZB structure ( Fig. 1).…”
Section: Calculation Detailsmentioning
confidence: 52%
“…As shown in Ref. 22, energetically the most favorable position of these surface atoms are the bridge positions in which the halogen atoms enter the positions of the missing selenium atoms in the ZB structure ( Fig. 1).…”
Section: Calculation Detailsmentioning
confidence: 52%
“…In this case, the influence of the surface microrelief and the dielectric properties of the environment on the characteristics of excitons localized in the near‐surface region can be described by introducing the effective permittivity, for example, according to the effective medium model 19 . And the increase in the binding energy of the surface exciton can be due to an increase in the ratio between the kinetic and potential energies of the quasiparticles, namely, the vanishing of the kinetic energy of the quasiparticle in one, two, or three coordinates and, thus, an increase in the potential energy of the particle with a dimensional limitation of its displacements 19,20 …”
Section: Resultsmentioning
confidence: 99%
“…19 And the increase in the binding energy of the surface exciton can be due to an increase in the ratio between the kinetic and potential energies of the quasiparticles, namely, the vanishing of the kinetic energy of the quasiparticle in one, two, or three coordinates and, thus, an increase in the potential energy of the particle with a dimensional limitation of its displacements. 19,20 F I G U R E 3 Photoluminescence spectra of (A) Bu m -nc-Si n (I) and (B) (NHC) m -nc-Si n (II): 1, dry nanoparticles before treatment; 2, dry nanoparticles after 5-min treatment by 7-MeV electron beam (Ф 1 = 1.25Á1,015 cm −2 ); 3, dry nanoparticles after 48-min treatment by 7-MeV electron beam (Ф 2 = 1.2Á1,016 cm −2 ); and 4, nanoparticles in suspension without treatment…”
Section: Sample II Curves 2 Andmentioning
confidence: 99%
“…In Ref. 5 it was shown that the most energetically favorable position of terminating atoms is the bridge position, in which the atoms enter the positions of missing Se atoms.…”
Section: Calculation Detailsmentioning
confidence: 99%
“…These properties are promising for various applications in nano-and optoelectronics (see Ref. 5 and references therein). It is known that the thermodynamically stable modification of bulk CdSe is the hexagonal wurtzite structure.…”
Section: Introductionmentioning
confidence: 99%